Parametric weighting functions - Enrico Diecidue; Ulrich Schmidt; Horst Zank (Kiel Institute for the World Economy (IfW), 2008)
This paper provides preference foundations for parametric weighting functions under rankdependent utility. This is achieved by decomposing the independence axiom of expected utility into separate meaningful properties. These conditions allow us to characterize rank-dependent utility with power and exponential weighting functions. Moreover, by allowing probabilistic risk attitudes to vary within the probability interval, a preference foundation for rank-dependent utility with parametric inverse-S shaped weighting function is obtained.
Keywords: D81; 330; Probability weighting function; Preference foundation; Rank-dependent utility; Comonotonic independence; Entscheidung bei Unsicherheit; Prospect Theory; Erwartungsnutzen; Theorie